The Pivotal Role of Jak/Stat and Irs/Pi3k Signaling Pathways in Neurodegenerative Diseases: Mechanistic Approaches to Polyphenols and Alkaloids - Echeverria-Morgado, J (Elsevier GmbH, 2023)
Background: Neurodegenerative diseases (NDDs) are characterized by progressive neuronal dysfunctionality which results in disability and human life-threatening events. In recent decades, NDDs are on the rise. Besides, conventional drugs have not shown potential effectiveness to attenuate the complications of NDDs. So, exploring novel therapeutic agents is an urgent need to combat such disorders. Accordingly, growing evidence indicates that polyphenols and alkaloids are promising natural candidates, possessing several beneficial pharmacological effects against diseases. Considering the complex pathophysiological mechanisms behind NDDs, Janus kinase (JAK), insulin receptor substrate (IRS), phosphoinositide 3-kinase (PI3K), and signal transducer and activator of transcription (STAT) seem to play critical roles during neurodegeneration/neuroregeneration. In this line, modulation of the JAK/STAT and IRS/PI3K signaling pathways and their interconnected mediators by polyphenols/alkaloids could play pivotal roles in combating NDDs, including Alzheimer s disease (AD), Parkinson s disease (PD), Huntington s disease (HD), stroke, aging, multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), depression and other neurological disorders. Purpose: Thus, the present study aimed to investigate the neuroprotective roles of polyphenols/alkaloids as multi-target natural products against NDDs which are critically passing through the modulation of the JAK/STAT and IRS/PI3K signaling pathways. Study design and Methods: A systematic and comprehensive review was performed to highlight the modulatory roles of polyphenols and alkaloids on the JAK/STAT and IRS/PI3K signaling pathways in NDDs, according to the PRISMA guideline, using scholarly electronic databases, including Scopus, PubMed, ScienceDirect, and associated reference lists. Results: In the present study 141 articles were included from a total of 1267 results. The results showed that phenolic compounds such as curcumin, epigallocatechin-3-gallate, and quercetin, and alkaloids such as berberine could be introduced as new strategies in combating NDDs through JAK/STAT and IRS/PI3K signaling pathways. This is the first systematic review that reveals the correlation between the JAK/STAT and IRS/PI3K axis which is targeted by phytochemicals in NDDs. Hence, this review highlighted promising insights into the neuroprotective potential of polyphenols and alkaloids through the JAK/STAT and IRS/PI3K signaling pathway and interconnected mediators toward neuroprotection. Conclusion: Amongst natural products, phenolic compounds and alkaloids are multi-targeting agents with the most antioxidants and anti-inflammatory effects possessing the potential of combating NDDs with high efficacy and lower toxicity. However, additional reports are needed to prove the efficacy and possible side effects of natural products. © 2023